1992
DOI: 10.2527/1992.7061667x
|View full text |Cite
|
Sign up to set email alerts
|

Live animal measurement of carcass traits by ultrasound: assessment and accuracy of sonographers

Abstract: The establishment and evaluation of an assessment system to accredit sonographers for measuring the carcass traits of subcutaneous fat depths and longissimus muscle area (LMA) on potential breeding animals by real-time ultrasound is described. Repeatability of operators, variation between the animal's left and right sides, and variations in technique were assessed from measurements and repeat measurements of 30 cattle by up to eight operators at three testing sessions. Accuracy of carcass data was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
2
16

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 6 publications
8
73
2
16
Order By: Relevance
“…Subcutaneous fat thickness at the rump (P8) and 12th/13th rib sites and cross-sectional area of M. longissimus at the 12th/13th rib site were recorded by ultrasound scanning (Robinson et al 1992) on entry to grow-out, at the commencement of finishing and at the end of the finishing phase as described by Upton et al (2001). All weights were directly off feed (full weights).…”
Section: Measurementsmentioning
confidence: 99%
“…Subcutaneous fat thickness at the rump (P8) and 12th/13th rib sites and cross-sectional area of M. longissimus at the 12th/13th rib site were recorded by ultrasound scanning (Robinson et al 1992) on entry to grow-out, at the commencement of finishing and at the end of the finishing phase as described by Upton et al (2001). All weights were directly off feed (full weights).…”
Section: Measurementsmentioning
confidence: 99%
“…Many researchers reported that accuracy of ultrasonic measured subcutan fat thickness and REA is quite good (BRETHOUR 1990, DUELLO et al 1990, SMITH et al 1992, PERKINS et al 1992a, PERKINS et al 1992b, WALDNER et al 1992, BRETHOUR 1992, ROBINSON 1992, RÖSLER et al 1996, MAY et al 2000, GREINER et al 2003. HARTJEN et al (1993) investigated a total of 648 young bulls of different breeds just before slaughter.…”
Section: Introductionmentioning
confidence: 99%
“…Even though ultrasonography is a widespread technique within the scientific community, many research reports still show inconsistent accuracy results, especially REA values (Brethour, 1992;Robinson et al, 1992;Busboom et al, 2000;Perry & Fox, 1997;May et al, 2000). Others consider this technique efficient only for REA estimation (Bullock et al, 1991;Bergen et al, 1997;Hassen et al, 1999a;Prado et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between live animal and carcass measurements can be attributed to several factors: method used for hide removal, which can remove quite a variable amount of backfat from the carcass; carcass hanging procedure, which will affect its conformation; rigor mortis development; inadequate REA measurement; incorrect separation of the section between the 12 th and 13 th ribs, and carcass wrapping (Brethour, 1992;Perkins et al, 1992a;Robinson et al, 1992;Bergen et al, 1996). Other factors such as ultrasound manufacturer and model, measurement magnitude (FT thickness and REA size) and technician's skill, may influence measurements' precision, as reported by several authors (Perkins et al, 1992b;Charagu et al, 2000;Greiner, 2001).…”
Section: Introductionmentioning
confidence: 99%